Role of Iron Phthalocyanine Coordination in Catecholamines Detection - Martin, Cibely S. [UNESP]; Rubira, Rafael J. G. [UNESP]; Silva, Jaqueline N. [UNESP]; Alessio, Priscila [UNESP] (Mdpi, 2021)
Catecholamines are an important class of neurotransmitters responsible for regularizing, controlling, and treating neural diseases. Based on control and diseases treatment, the development of methodology and dives to sensing is a promissory technology area. This work evaluated the role of iron phthalocyanine coordination (FePc) with the specific groups from catecholamine molecules (L-dopa, dopamine, epinephrine, and the amino acid tyrosine) and the effect of this coordination on electrochemical behavior. The in situ coordination analysis was performed through isotherms pi-A of FePc Langmuir films in the absence and presence of catecholamines. The pi-A isotherm indicates a strong interaction between FePc monolayer and L-Dopa and DA, which present a catechol group and a side chain with a protonated amino group (-NH3+). These strong interactions with catechol and amine groups were confirmed by characterization at the molecular level using the surface-enhanced Raman spectroscopy (SERS) from a Langmuir-Schaefer monolayer deposited onto Ag surfaces. The electrochemical measurements present a similar tendency, with lower oxidation potential observed to DA>L-Dopa>Ep. The results corroborate that the coordination of the analyte on the electron mediator surface plays an essential role in an electrochemical sensing application. The FePc LS film was applied as a sensor in tablet drug samples, showing a uniformity of content of 96% for detecting active compounds present in the L-Dopa drug samples.
Keywords: catecholamines; iron coordination; phthalocyanines; electrochemical sensing